Alegoria a alegoreza - przyczynek do dyskusji o poprawności terminów stosowanych w badaniach nad alegorezą grecką, żydowską i wczesnochrześcijańską - Zieliński, Jacek (Vox Patrum, 2023)
The purpose of this article is to contrast the method of Greek allegoresis (Heraclitus the Allegorist) with Jewish allegoresis, as reconstructed from the works of Philo of Alexandria and early Christianity (Origen). This reconstruction allowed me, in the section entitled allegory and allegoresis, to make the following theses: firstly, the terms allegory and allegoresis, without good reasons, are used interchangeably in the literature . And yet, the procedure of allegorising (allegory) a text differs significantly from the method of explaining the text in an allegorical way. For this reason, I have proposed a further theses of (1) the need to distinguish between the above procedures unambiguously and (2) to introduce specific terms to capture the difference between the Greek, Jewish and early Christian allegoresis. For this purpose, I have introduced concepts used in hermeneutics, namely: allegoresis sacra and allegoresis prophana. In the following sections of the article, I discussed the specific features of each type of ancient allegoresis: Greek, Jewish and Christian. All three forms of allegoresis aim to present a commentary that meets the standards of rationality developed by ancient science (philosophy), i.e. to eliminate all illogicalities, anthropomorphisms or anthropopathisms (with reference to God) and to extract a universal message from the text e.g. of the ‚Bible’. The difference that emerges between them, leads to the conclusion that, in contrast to the Greek allegoresis, Philo and Origenes recognize the validity of the literal sense (the letter of the text) in a different way; they make sure to preserve it . It can be claimed that with Origen the allegoretic method attained its fullest or mature form, (1) pointing to the three senses of the text: the literal (soma), moral (psyche), and mystical-philosophical (pneuma), and (2) combining the allegoresis sacra and prophana into a single method of reading and interpreting the text of the Scripture.